(untitled) (Fiep Bulletin - online, 2013)
The present exploratory type study has as its investigation starting point the problem over the building of the pieces of knowledge of the physical education teachers’ profession. To answer this question, it was analyzed the speech of teachers who collaborated with the extension project from the Universidade Estadual de Campinas together with the municipal education network of Londrina-Pr. Asemi-structured interview was used as a tool to collect the data, which was made before and after their part in the project. The analyses allowed us to conclude that physical education teachers build their knowledge based on their life histories, and their experience on working at a school field. Another aspect shown in these analyses is that when facing each of the school institutions, teachers also build specific knowledge that become part of both individual and group experience in the educational field. Physical education teachers have little autonomy in their pedagogical work. After one year of critical reflexive work experienced in the extension project, teachers showed that their ideas were now supported by rational justification over their actions aiming to the construction of new knowledge and the search for a professional autonomy. Thus, it was concluded that pieces of knowledge are result of a whole professional career building in a professional development process. The pieces of knowledge become competence whenever it is permeated with consideration, criticisms and research.